Product Naming as a Business Communication Practice: Legal and Islamic Business Ethics Perspectives on Products Inconsistent with Shari’ah Principles - Dodon Alfiander; Elimartati; Sulastri Caniago; Yustiloviani (UIN Mahmud Yunus Batusangkar, 2026)
The naming (labelling) of food and beverage products is not merely a matter of marketing strategy but also encompasses legal, ethical, and moral dimensions within the Muslim community. The growing trend of using distinctive and unconventional product names that reference alcoholic beverages, prohibited animals, symbols of disbelief (kufr), or erotic elements raises important concerns regarding honesty, manipulation, and business actors' compliance with the principles of Islamic law (Shari’ah). This study employs a library research method using a normative approach to examine the regulations governing the Halal Product Assurance System, the Decree of the Halal Product Assurance Organizing Agency (BPJPH) on the Halal Product Assurance System, technical standards for halal food, and the fatwas of the Indonesian Ulama Council (MUI) concerning product names, forms, and packaging, complemented by the literature on Islamic business ethics. The findings demonstrate that product names inconsistent with Shari’ah principles have the potential to violate both statutory regulations and religious fatwas while simultaneously disregarding the principles of justice, honesty, and transparency that underpin Islamic business ethics. Furthermore, such practices contribute to the social normalization of symbols that contradict the values of halal and halalan thayyiban, thereby diminishing society's moral sensitivity to the distinction between what is lawful (halal) and unlawful (haram). The novelty of this study lies in positioning product naming as a form of commercial communication that directly influences public perception, social habituation, and the preservation of maqashid al-Shari’ah within the contemporary public sphere, rather than viewing it merely as an administrative issue in the halal certification process.